The Village Government's Contribution to Raising Community Awareness of Land and Building Tax Payment - Sopyan, Ence; Tomy, Chairian (International Journal of Public Administration and Policy, 2025)
There are still a lot of people in Penengahan District who have not paid their taxes or who are paying them late. People don't pay because their economy is still in need, and they lack a sense of nationality, among other reasons. In order to remedy this, the Village Government must be able to take advantage of the area's land and construction tax potential and encourage taxpayers to fulfill their tax-payment duties. Leadership and governance are the theories that were applied in this study. Governance as a set of social and political processes involving the government and society in a variety of areas pertaining to societal interests and government engagement in these interests. A qualitative approach was taken in this study. After doing observations, the researcher conducted interviews and provided documentation to back up her findings. The researcher collected five informants—three main informants and two support informants—by using purposive sampling to identify the informants. According to the study's findings, the village government plays a crucial role in helping those who are less aware of the value of taxpayers in Penengahan District by educating the public about paying taxes, offering advice, and simultaneously assessing tax receipts.